2020
DOI: 10.1111/aji.13287
|View full text |Cite
|
Sign up to set email alerts
|

Zim CHIC: A cohort study of immune changes in the female genital tract associated with initiation and use of contraceptives

Abstract: Problem Contraceptive hormones are systemically active, potent, and likely to invoke biological responses other than known fertility regulation impacts. We hypothesized that initiation of depot medroxyprogesterone acetate (DMPA) would increase genital HIV‐target‐cells and soluble immune mediators compared with baseline and initiation of other contraceptive methods. Method of Study We collected cervical cytobrushes and cervicovaginal fluid from healthy Zimbabwean women a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 28 publications
2
19
0
Order By: Relevance
“…Achilles et al enrolled women that were STI/HIV negative with regular menstrual cycles seeking contraception counseling in Harare, Zimbabwe, excluding those with recent hormonal contraceptive use. 29 Use of DMPA ( N = 38) associated with decreased cervical CD4+ T cells (percent and total cell numbers at days 30 and 180 after DMPA initiation, respectively) and CD11c+ antigen‐presenting cells after 180 days, but no changes in CD4+ and CD8+ T cells expressing CCR5. In terms of soluble factors, they observed a significant increase in IL‐10 at day 30, and a significant decrease in IL‐1β, and a trending decrease in IL‐8 at days 30 and 180 after DMPA initiation.…”
Section: Dmpa Use and On The Immunology Of The Vaginal Environmentmentioning
confidence: 93%
See 2 more Smart Citations
“…Achilles et al enrolled women that were STI/HIV negative with regular menstrual cycles seeking contraception counseling in Harare, Zimbabwe, excluding those with recent hormonal contraceptive use. 29 Use of DMPA ( N = 38) associated with decreased cervical CD4+ T cells (percent and total cell numbers at days 30 and 180 after DMPA initiation, respectively) and CD11c+ antigen‐presenting cells after 180 days, but no changes in CD4+ and CD8+ T cells expressing CCR5. In terms of soluble factors, they observed a significant increase in IL‐10 at day 30, and a significant decrease in IL‐1β, and a trending decrease in IL‐8 at days 30 and 180 after DMPA initiation.…”
Section: Dmpa Use and On The Immunology Of The Vaginal Environmentmentioning
confidence: 93%
“…All of these studies included self‐selection of contraceptive method instead of randomization to contraception arm. Achilles et al enrolled women that were STI/HIV negative with regular menstrual cycles seeking contraception counseling in Harare, Zimbabwe, excluding those with recent hormonal contraceptive use 29 . Use of DMPA ( N = 38) associated with decreased cervical CD4+ T cells (percent and total cell numbers at days 30 and 180 after DMPA initiation, respectively) and CD11c+ antigen‐presenting cells after 180 days, but no changes in CD4+ and CD8+ T cells expressing CCR5.…”
Section: Dmpa Use and On The Immunology Of The Vaginal Environmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The only user-directed contraceptive used by men is the penile condom, whose barrier function directly reduces HIV risk and whose impacts on penile immunology or [104,105] the penile microbiome have not been studied to our knowledge. In contrast, several contraceptive choices employed by women have important immune effects on the female genital tract.…”
Section: Contraceptionmentioning
confidence: 99%
“…While global guidance has treated DMPA-IM, DMPA-SC, and NET-EN similarly, a recent review of pharmacokinetic, biologic, and epidemiologic differences in MPA-and NET-based progestin-only injectable contraceptives concluded that they are likely to act differently relative to potential HIV acquisition in women, based on most of the available biological activity and epidemiological data (12). Recent findings from the Zim-CHIC study suggest that women who initiate DMPA and NET-EN exhibit some differences in genital tract immune mediators (both soluble and cellular) (13). However, changes were limited compared to those observed among women initiating the use of a copper IUD.…”
Section: Introductionmentioning
confidence: 99%